Worked out Results of IPCCR Framework for AMS Projects - Rao Kosiganti, Srinivasa; Y. Prasanth, Dr (International Journal of Engineering and Technology, 2018)
The IPCCR framework that was designed to reduce CAPEX and OPEX of Application Support and Maintenance Projects, has helped to understand Incident, Problem, Change, Configuration and Release and directly impacts the costs that are accrued.Â Using Proper Incident Management, Problem Management, Change Management, Configuration Management and Release Management, which are the key ingredients of ITIL V3.2 and DevOps reduces the costs of Capital Expenses and Operational Expenses.Â The important concept of Known Error Database will subsequently reduce the Operational Expenses as much as possible.Â Â